Assessing the Impact of Peer Interaction on the English Speaking Proficiency of the 2nd Semester Students of English Education Study Program at the Faculty of Teacher Training and Education, Sriwijaya University - Fikry, Muhammad Adzka; Zuraida Zuraida (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to examine the impact of peer interaction on English-speaking proficiency among second-semester students of the English Education Study Program at Sriwijaya University. The research addresses the persistent challenge of low speaking confidence and fluency among EFL learners, particularly within Indonesian higher education contexts. Using a mixed-method design, the study integrates quantitative and qualitative approaches to gain both measurable and in-depth insights. The quantitative component employed a correlational design involving 29 students, using a 15-item Likert-scale questionnaire to assess variables such as confidence, motivation, anxiety reduction, and linguistic development. The qualitative component, based on a phenomenological approach, involved semi-structured interviews with 12 participants to explore personal experiences and perceptions regarding peer interaction in speaking activities. The results revealed a strong positive correlation between the frequency of peer interaction and students’ self-rated improvement in speaking proficiency. Quantitative findings indicated that over 80% of respondents perceived increased confidence and motivation, while qualitative analysis identified four dominant themes: enhanced confidence, affective comfort, linguistic enrichment, and anxiety reduction. These findings affirm Vygotsky’s Sociocultural Theory, highlighting that language learning is socially mediated and strengthened through collaborative dialogue.The study concludes that structured peer interaction significantly enhances both the affective and linguistic aspects of EFL learners’ speaking performance. Theoretically, the research extends sociocultural learning frameworks to the Indonesian higher education context; practically, it recommends the integration of peer-based speaking activities into communicative language teaching. Future research should employ longitudinal designs and include larger, cross-institutional samples to further explore the long-term and contextual dynamics of peer interaction in language acquisition.